2018
DOI: 10.1039/c8ta00526e
|View full text |Cite
|
Sign up to set email alerts
|

15% efficient carbon based planar-heterojunction perovskite solar cells using a TiO2/SnO2bilayer as the electron transport layer

Abstract: Low-temperature printable carbon based planar-heterojunction perovskite solar cells with efficiencies exceeding 15% were demonstrated by using a TiO2/SnO2bilayer as ETL together with CuPc as HTL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 80 publications
0
51
0
Order By: Relevance
“…The ETL plays an important role in extracting electrons from the perovskite layer. It can prevent contact between the fluorine-doped SnO 2 (FTO) and perovskite layer to avoid the recombination of electrons and holes, and reduce energy loss at the interface [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The ETL plays an important role in extracting electrons from the perovskite layer. It can prevent contact between the fluorine-doped SnO 2 (FTO) and perovskite layer to avoid the recombination of electrons and holes, and reduce energy loss at the interface [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Both TiO 2 and ZnO are unstable under UV light exposure because of their high photocatalytic activity. 24 Typically, TiO 2 requires a high temperature (up to 500 °C) and long (2–5 h) annealing procedure to convert it into the conductive phase, hindering its use in final iOSC products, where roll-to-roll industrial processing on flexible substrates (temperature processing below 200 °C) is employed. 25 Furthermore, iOSCs using TiO 2 or ZnO ETLs usually suffer from light-soaking problems; that is, very poor device performance of these iOSCs is observed in the absence of UV sources.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, perovskite solar cells (PSCs) have been recognized as the most promising alternatives to conventional silicon solar cells due to high conversion efficiency, low manufacturing cost, and simple process [1][2][3][4][5][6][7]. As for typical planar heterojunction PSCs composed of working electrode (cathode)/hole blocking layer/perovskite layer/electron blocking layer/counter electrode (anode), the hole blocking layer plays an important role in extracting electrons from the perovskite layer and, as well as, suppressing recombination of holes and electrons between the perovskite layer and FTO [8][9][10][11]. A uniform, pinhole-free and well electrically conductive hole blocking layer is highly demanded for well performed planar heterojunction PSCs [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…As for typical planar heterojunction PSCs composed of working electrode (cathode)/hole blocking layer/perovskite layer/electron blocking layer/counter electrode (anode), the hole blocking layer plays an important role in extracting electrons from the perovskite layer and, as well as, suppressing recombination of holes and electrons between the perovskite layer and FTO [8][9][10][11]. A uniform, pinhole-free and well electrically conductive hole blocking layer is highly demanded for well performed planar heterojunction PSCs [8,12]. Liao et al found that the pinholes on the surface of the single SnO 2 hole blocking layer coating on the rough FTO substrate were still hard to eliminate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation